Benefits of Alumni / Priestly Lanting Layang ... [et al.] - Layang, Priestly Lanting; Abang Shamsudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
Benefits that you get by joining Alumni Association after graduation. Here are some benefits that you get for being an alumni: 01. Travel Discounts - Malaysia Airlines & Firefly extend a discount of 15% on airfares to all UiTM alumni registered in the MyAlumni UiTM mobile app.